ANO1: More Than Just Calcium-Activated Chloride Channel in Cancer - Guo, Saisai; Zhang, Linna; Li, Na (Frontiers in Oncology, 2022)
ANO1, a calcium-activated chloride channel (CACC), is also known as transmembrane protein 16A (TMEM16A). It plays a vital role in the occurrence, development, metastasis, proliferation, and apoptosis of various malignant tumors. This article reviews the mechanism of ANO1 involved in the replication, proliferation, invasion and apoptosis of various malignant tumors. Various molecules and Stimuli control the expression of ANO1, and the regulatory mechanism of ANO1 is different in tumor cells. To explore the mechanism of ANO1 overexpression and activation of tumor cells by studying the different effects of ANO1. Current studies have shown that ANO1 expression is controlled by 11q13 gene amplification and may also exert cell-specific effects through its interconnected protein network, phosphorylation of different kinases, and signaling pathways. At the same time, ANO1 also resists tumor apoptosis and promotes tumor immune escape. ANO1 can be used as a promising biomarker for detecting certain malignant tumors. Further studies on the channels and the mechanism of protein activity of ANO1 are needed. Finally, the latest inhibitors of ANO1 are summarized, which provides the research direction for the tumor-promoting mechanism of ANO1.